Lifetime prevalence and potential determinants of psychotic experiences in the general population of Qatar. Issue 7 (28th May 2020) - Khaled, Salma M.; Wilkins, Stacy Schantz; Woodruff, Peter
Abstract: Background: To estimate the lifetime prevalence and potential determinants of psychotic experience(s) (PEs) in the general population of Qatar – a small non-war afflicted, conservative, high-income, middle-eastern country with recent rapid urbanization including an influx of migrants. Methods: A probability-based sample ( n = 1353) of non-migrants and migrants were interviewed face-to-face and administered a 7-item psychosis screener adapted from the Composite International Diagnostic Interview, the Kessler 6-item psychological distress scale, and the 5 items assessing odd (paranormal) beliefs and magical thinking (OBMT) from the Schizotypal Personality Questionnaire. Using bivariate and logistic regression analyses, lifetime prevalence rates of PEs were estimated then compared before and after adjustment for socio-demographics, Arab ethnicity, psychological distress, and OBMT. Results: Prevalence of PEs was 27.9%. Visual hallucinations were most common (12.8%), followed by persecutory delusions (6.7%) and auditory hallucinations (6.9%). Ideas of reference (3.6%) were least prevalent. PEs were significantly higher in Arabs (34.7%) compared with non-Arabs (16.4%, p < 0.001) with the exception of ideas of reference and paranoid delusions. Female gender was associated with a higher prevalence of PEs in the Arab group only ( p < 0.001). Prevalence of PEs was significantly higher among Arabs (48.8% v. 15.8%, p < 0.001) and non-Arabs (35.2% v. 7.3%, p < 0.001) with OBMT. Arab ethnicity (OR = 2.10, p = 0.015), psychological distress (OR = 2.29 p = 0.003), and OBMT (OR = 6.25, p < 0.001) were independently associated with PEs after adjustment for all variables. Conclusions: Ethnicity, but not migration was independently associated with PEs. Evidence linking Arab ethnicity, female gender, and psychological distress to PEs through associations with OBMT was identified for future prospective investigations.